Amplification of the Capacitance Containing Nematic Liquid Crystal Embedded with Metal Nanoparticles. (16th February 2012) - Kobayashi, Shunsuke; Sakai, Yoshio; Miyama, Tomohiro; Nishida, Naoto; Toshima, Naoki
Abstract : Herein, we report the dielectric properties of liquid crystal cells embedded with the nanoparticles of Pd, where each of which is covered with a diffusion cloud. It is shown that an amplification of the capacitors with these media occurs with the gain, A c = 12.5, when the concentration of nanoparticles is 0.3 wt% and in the frequency region below the dielectric relaxation frequency, 158.5 Hz. This phenomenon is explained by an equivalent circuit model together with a compatible explanation of the dielectric strength and the relaxation time. It is claimed that the occurrence of the capacitance amplification may be attributed to a special nature of the oscillating extra charges, which appear in the region between the host medium and inclusion, and produces an effective negative dielectric constant of the special nanoparticles. This explanation was made by formulating an independent auxiliary equivalent circuit equation that enables to determine the numerical condition of the production of the negativity in the dielectric constant of inclusions (nanoparticles), and, thus, we succeeded in getting the numerical value of this dielectric constant and that of the gain of the capacitance amplification.